Hospital workers bypass traditional occupational injury reporting systems when reporting patient and visitor perpetrated (type II) violence. Issue 10 (13th July 2016) - Pompeii, Lisa A.; Schoenfisch, Ashley; Lipscomb, Hester J.; Dement, John M.; Smith, Claudia D.; Conway, Sadie H.
Abstract : Background: Under‐reporting of type II (patient/visitor‐on‐worker) violence by workers has been attributed to a lack of essential event details needed to inform prevention strategies. Methods: Mixed methods including surveys and focus groups were used to examine patterns of reporting type II violent events among ∼11, 000 workers at six U.S. hospitals. Results: Of the 2, 098 workers who experienced a type II violent event, 75% indicated they reported. Reporting patterns were disparate including reports to managers, co‐workers, security, and patients' medical records—with only 9% reporting into occupational injury/safety reporting systems. Workers were unclear about when and where to report, and relied on their own "threshold" of when to report based on event circumstances. Conclusions: Our findings contradict prior findings that workers significantly under‐report violent events. Coordinated surveillance efforts across departments are needed to capture workers' reports, including the use of a designated violence reporting system that is supported by reporting policies. Am. J. Ind. Med. 59:853–865, 2016. © 2016 Wiley Periodicals, Inc.